Persistence in corporate networks - Mishael Milaković; Matthias Raddant; Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
We examine the bipartite graphs of German corporate boards in 1993, 1999 and 2005, and identify cores of directors who are highly central in the entire network while being densely connected among themselves. The novel feature of this paper is the focus on the dynamics of these networks. Germany's corporate governance has experienced significant changes during this time, and there is substantial turnover in the identity of core members, yet we observe the persistent presence of a network core, which is even robust to changes in the tail distribution of multiple board memberships. Anecdotal evidence suggests that core persistence originates from the board appointment decisions of largely capitalized corporations.
Keywords: 330